Rural Women Entrepreneurship based on Tourism Village through Post-Disaster Socio-Ecological Capital - Dony Arung Triantoro; Ashabul Yamin Asgha; Futri Syam; Anhar Fazri (Sodality: Jurnal Sosiologi Pedesaan, 2023)
Women have always been considered in several studies as the most vulnerable group to disaster risk and less involved in the post-disaster recovery process. This paper aims to find out and analyze the entrepreneurial activities of rural women who joined the management of Nusa Tourism Village as one of the post-disaster economic recovery efforts. The main question that will be answered in this study is how rural women are involved in entrepreneurial activities based on tourism villages after the tsunami. To answer this question, this paper uses qualitative methods with a constructivist paradigm and narrative approach. Data collection was conducted through interviews, observation, and documentation. The results showed that women of Nusa Village carried out tourism village-based entrepreneurial activities through socio-ecological capital. This socio-ecological capital consists of elements of social capital in the form of social relations, beliefs, collective norms, and collective actions. The element of ecological capital is in the form of the utilization of land, water, plants, and household waste which is packaged through various tour packages. This study concludes that socio-ecological capital is an important capital for rural women in carrying out entrepreneurial activities to recover the post-disaster economy.